Criminal Responsibility of Children in Crimes of Child Sexual Violence: A Study of Decision Number XX/PID.Sus-Anak/2025/PN TJK - Fakhri Qolby Aminullah Fikri (Jurnal Terekam Jejak, 2026)
This study aims to analyze the criminal liability of a juvenile offender in a child sexual violence case and the judge's legal considerations in Decision Number XX/Pid.Sus-Anak/2025/PN Tjk. The research employed normative juridical and empirical approaches. Data were collected through library research and field research. The results indicate that the imposition of criminal liability on the juvenile offender in Decision Number XX/Pid.Sus-Anak/2025/PN Tjk was in accordance with the applicable laws and regulations. The defendant was found guilty of violating Article 81 paragraph (2) in conjunction with Article 76D of Law Number 17 of 2016 concerning Child Protection and was sentenced to two years of imprisonment accompanied by job training. Although diversion was not applicable because the statutory requirements were not fulfilled, the court upheld the principle of the best interests of the child by emphasizing guidance and rehabilitation. The judge's decision was based on juridical considerations, including the facts presented at trial, evidence, and applicable legal provisions, as well as non-juridical considerations, including the child's age, psychological condition, family background, remorse, and the impact of the offense on the victim.